2001
DOI: 10.1111/1468-0297.00626
|View full text |Cite
|
Sign up to set email alerts
|

On the Policy Implications of Endogenous Technological Progress

Abstract: One of the most well-known empirical regularities in the R&D-productivity literature is the existence of substantial under-investment in R&D. This strongly suggests that government should actively promote research activities. However, the so-called`quality-ladders' models of endogenous technological progress are inconsistent with this observation. In an extreme case, Grossman and Helpman (1991, Ch.4) suggest that R&D should always be taxed irrespective of the size of quality improvement. This paper attempts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 21 publications
1
88
0
Order By: Relevance
“…This section calculates the socially optimal R&D share of GDP in (34). Figure 3 plots the socially optimal R&D share for each set of parameter values in Table 2 that corresponds to r equal 0.30.…”
Section: Socially Optimal Level Of Randd Spendingmentioning
confidence: 99%
See 1 more Smart Citation
“…This section calculates the socially optimal R&D share of GDP in (34). Figure 3 plots the socially optimal R&D share for each set of parameter values in Table 2 that corresponds to r equal 0.30.…”
Section: Socially Optimal Level Of Randd Spendingmentioning
confidence: 99%
“…In a sense, this finding is not surprising given the large estimated social return to R&D. Optimal R&D share increases in ξ in Figure 3 because a larger ξ implies a larger Table 2. Applying the log approximation x x ≈ + ) 1 ln( to (C4) and combining it with (34), it can be shown that …”
Section: Socially Optimal Level Of Randd Spendingmentioning
confidence: 99%
“…In a dynamic general-equilibrium model, Judd (1985) …nds that the optimal patent length is in…nite while Iwaisako and Futagami (2003) and Futagami and Iwaisako (2007) …nd that the optimal patent length can be …nite in a version of the Romer model. Kwan and Lai (2003) show that extending the e¤ective lifetime of patent would lead to a substantial increase in R&D and welfare whereas Li (2001) and O'Donoghue and Zweimuller (2004) consider the e¤ects of patent breadth on R&D and economic growth. Dinopoulos and Syropoulos (2007) and Davis and Sener (2012) analyze the e¤ects of rent protection activities on innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we incorporate into the model mainly two features (a) patent breadth as in Li (2001) and (b) aggregate uncertainty in the innovation process. Given that the quality-ladder model has been well-studied, the familiar components of the model will be briefly described to conserve space while the new features will be described in more details below.…”
Section: The Modelmentioning
confidence: 99%
“…Li (2001) generalizes the policy environment to allow for incomplete patent breadth ) 1 , 0 (  b against imitation. Due to incomplete patent protection, the former industry leader's productivity increases by a factor b z  1 (i.e., her productivity becomes…”
Section: Final Goodsmentioning
confidence: 99%